2021
DOI: 10.21083/ajote.v10i1.6521
|View full text |Cite
|
Sign up to set email alerts
|

The Paradox of Ghanaian High School Mathematics Teachers’ Perspectives on ICT Use

Abstract: The paper sought to investigate the perceived use of Information Communication Technology (ICT) of high school mathematics teachers in Ghana. A hundred high school mathematics teachers from 20 public schools,10 each located in the rural and urban areas respectively in the Central region of Ghana, were stratified and used in the study. A questionnaire and semi-structured interviews were used to collect data. The result of the study indicated low levels of perceived knowledge/skills of ICT use by high school mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…ICT tools are viewed as valuable resources that can provide interactive and visual representations, promote collaborative learning, and cater to diverse learning styles (Picciano, 2017;Yelland, 2013). Teachers perceive that ICT integration can enhance students' problem-solving skills, critical thinking abilities, and overall academic achievement (Mensah, 2017). Even though previous studies have identified factors such as limited access to technology, internet connectivity, inadequate ICT infrastructure, and insufficient resources as significant barriers to ICT integration (Chigona & Chigona, 2012;Tay & Mensah-Wonkyi, 2018).…”
Section: Essence Of Perception and Readiness In Integration Of Ict To...mentioning
confidence: 99%
“…ICT tools are viewed as valuable resources that can provide interactive and visual representations, promote collaborative learning, and cater to diverse learning styles (Picciano, 2017;Yelland, 2013). Teachers perceive that ICT integration can enhance students' problem-solving skills, critical thinking abilities, and overall academic achievement (Mensah, 2017). Even though previous studies have identified factors such as limited access to technology, internet connectivity, inadequate ICT infrastructure, and insufficient resources as significant barriers to ICT integration (Chigona & Chigona, 2012;Tay & Mensah-Wonkyi, 2018).…”
Section: Essence Of Perception and Readiness In Integration Of Ict To...mentioning
confidence: 99%
“…Interactive tools like virtual classrooms, discussion forums, and online group projects encourage active participation and peer learning, essential for developing social and communication skills in a digital age (Andreev et al, 2020;ŞENYİĞİT & SERİN, 2022). Furthermore, the use of data analytics and educational technologies enables educators to tailor their teaching strategies to meet the individual needs of learners, enhancing the learning experience and outcomes (Mensah & Agyei, 2021). Thus, the integration of ICT in education is not just a trend but a critical component in preparing students to thrive in a technologically advanced society, making this topic of paramount importance in educational discourse.…”
Section: Introductionmentioning
confidence: 99%
“…The use of Information Communication and Technologies (ICTs) has become a catchphrase in contemporary education. The rapid growth and expansion of ICTs have significantly changed narratives in virtually all human endeavours and have affected the demands of modern societies (Mensah, 2017). Many countries all over the world have continued to push for the full integration of ICTs into education due to the lack of teaching resources and the enablement that ICTs offer.…”
mentioning
confidence: 99%
“…ICT takes the low and high calibre students to heights unknown. Thus, it's no gainsaying that integration of ICTs into mathematics instructions can potentially change pedagogical methods radically with the corresponding improvement in students' learning outcomes (Mensah, 2017). Therefore, The need to enhance mathematics instruction through the use ICTs for improving the performance of students in the subject in Nigeria can no longer be paid lip service.…”
mentioning
confidence: 99%